Puss in boots - Cauley, Lorinda Bryan; Perrault, Charles, 1628-1703. (San Diego : Harcourt Brace Jovanovich, 1986)
A retelling of the French fairy tale in which a clever cat wins his master a fortune and the hand of a princess.
3.5
K-3
K-3
Wilson's Children
School Library Journal
Publisher's Weekly
Keywords: Fairy tales; Folklore -- France; Fairy tales; Folklore -- France